Identification and Characterization Different Type of Plastics Waste Using X-Ray Diffraction and X-Ray Fluorescence - Shawbo A. Abubaker; Faten chaqmaqche; Akram Taha (ARO-The Scientific Journal of Koya University, 2021)
In this study, different types of polymers in post-consumer plastics with pure plastics have been studied. High-density polyethylene (HDPE1, HDPE2), Polyvinyl chloride (PVC3, PVC4), Polyethylene terephthalate (PET5, PET6) and Polypropylenes (PP7, PP8) were compared using X-ray diffraction (XRD) and X-ray fluorescence (XRF) techniques. XRF has shown the spectral in k-lines of polymer materials present in plastics waste. The peak intensity and degree of crystallinity of commercial polymers are varied using X-ray diffraction analysis. The intensity not attributable to the crystalline peaks may be regarded as the amorphous scattering and used as a template in analyzing the diffraction pattern of the samples. The XRD analysis helps to provide characteristic spectral lines whose intensities vary with the type of each constituent polymer. The combined use of XRD, and XRF techniques yielded very useful and effective results for a commercial plastic management.